The STRUGGLE OF MUNIBA MAZARI IN FACING INEQUALITY: A CRITICAL DISCOURSE ANALYSIS OF MUNIBA’S SPEECH - Daiya Setianni G. Putri; Santa Maya Pramusita (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2018)
ABSTRACTGender inequality is the one of global issues that still happen to this day. Research has shown that inequality regarding gender mostly occurs in developing countries, causing many women on those countries lose many of their rights. Sadly, this also happens to Pakistani disabled Woman, Muniba Mazari. During her lifetime, she has received many unequal treatment from her family and husband. This paper aims to find out the struggle of Muniba Mazari in facing gender inequality so that the readers can get clear depiction on how women are treated unequally in some countries and to improve the readers’ awareness in responding to such social problem. This research was applied qualitative descriptive method by presenting the inequality based on Muniba Mazari’s speech. The applied theory came from Bourdieu of social structure and doxa, as well as Appraisal Theory will be used as a tool in disclosing the inequality. The results show that the inequality that Muniba got from her family and husband are sourced from the strong social structure and doxa spreading around her. Meanwhile, the appraisal theory shows that the most data implies unhappiness as Muniba did not accept her condition and felt oppressed of her previous life and unhappy marriage. Keyword: Critical Discourse Analysis, Muniba Mazari’s speech, Inequality